The mechanistic bases of the power–time relationship: muscle metabolic responses and relationships to muscle fibre type. (1st May 2016) - Vanhatalo, Anni; Black, Matthew I.; DiMenna, Fred J.; Blackwell, Jamie R.; Schmidt, Jakob Friis; Thompson, Christopher; Wylie, Lee J.; Mohr, Magni; Bangsbo, Jens; Krustrup, Peter; Jones, Andrew M.
Abstract : Key points: The power‐asymptote (critical power; CP) of the hyperbolic power–time relationship for high‐intensity exercise defines a threshold between steady‐state and non‐steady‐state exercise intensities and the curvature constant ( W ′) indicates a fixed capacity for work >CP that is related to a loss of muscular efficiency. The present study reports novel evidence on the muscle metabolic underpinnings of CP and W ′ during whole‐body exercise and their relationships to muscle fibre type. We show that the W ′ is not correlated with muscle fibre type distribution and that it represents an elevated energy contribution from both oxidative and glycolytic/glycogenolytic metabolism. We show that there is a positive correlation between CP and highly oxidative type I muscle fibres and that muscle metabolic steady‐state is attainable CP. Our findings indicate a mechanistic link between the bioenergetic characteristics of muscle fibre types and the power–time relationship for high‐intensity exercise. Abstract: We hypothesized that: (1) the critical power (CP) will represent a boundary separating steady‐state from non‐steady‐state muscle metabolic responses during whole‐body exercise and (2) that the CP and the curvature constant ( W ′) of the power–time relationship for high‐intensity exercise will be correlated with type I and type IIx muscle fibre distributions, respectively. Four men and four women performed a 3 min all‐out cycling test for the estimation of CP and constant work rate (CWR) tests slightly >CP until exhaustion ( T lim ), slightly CP T lim isotime to test the first hypothesis. Eleven men performed 3 min all‐out tests and donated muscle biopsies to test the second hypothesis. Below CP, muscle [PCr] [42.6 ± 7.1  vs . 49.4 ± 6.9 mmol (kg d.w.) −1 ], [La − ] [34.8 ± 12.6  vs . 35.5 ± 13.2 mmol (kg d.w.) −1 ] and pH (7.11 ± 0.08 vs . 7.10 ± 0.11) remained stable between ∼12 and 24 min ( P  > 0.05 for all), whereas these variables changed with time >CP such that they were greater [[La − ] 95.6 ± 14.1 mmol (kg d.w.) −1 ] and lower [[PCr] 24.2 ± 3.9 mmol (kg d.w.) −1 ; pH 6.84 ± 0.06] ( P  < 0.05) at T lim (740 ± 186 s) than during the <CP trial. The CP (234 ± 53 W) was correlated with muscle type I ( r  = 0.67, P  = 0.025) and inversely correlated with muscle type IIx fibre proportion ( r  = −0.76, P  = 0.01). There was no relationship between W ′ (19.4 ± 6.3 kJ) and muscle fibre type. These data indicate a mechanistic link between the bioenergetic characteristics of different muscle fibre types and the power–duration relationship. The CP reflects the bioenergetic characteristics of highly oxidative type I muscle fibres, such that a muscle metabolic steady‐state is attainable below and not above CP. Key points: The power‐asymptote (critical power; CP) of the hyperbolic power–time relationship for high‐intensity exercise defines a threshold between steady‐state and non‐steady‐state exercise intensities and the curvature constant ( W ′) indicates a fixed capacity for work >CP that is related to a loss of muscular efficiency. The present study reports novel evidence on the muscle metabolic underpinnings of CP and W ′ during whole‐body exercise and their relationships to muscle fibre type. We show that the W ′ is not correlated with muscle fibre type distribution and that it represents an elevated energy contribution from both oxidative and glycolytic/glycogenolytic metabolism. We show that there is a positive correlation between CP and highly oxidative type I muscle fibres and that muscle metabolic steady‐state is attainable CP. Our findings indicate a mechanistic link between the bioenergetic characteristics of muscle fibre types and the power–time relationship for high‐intensity exercise.